2003
DOI: 10.1046/j.1526-4610.2003.03202.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Primary Headache in the Emergency Department

Abstract: The overwhelming majority of patients who present to an emergency department with acute primary headache have migraine, but the majority of patients receive a less specific diagnosis and a treatment that is correspondingly nonspecific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 11 publications
7
69
1
1
Order By: Relevance
“…This is because most of the data collected in this field are obtained with retrospective studies. From this point of view it has been shown that the incidence of primary headache (PH) diagnosis is lower in the ED than in the general population [1][2][3][4][5][6][7][8][9].…”
Section: Prevalencementioning
confidence: 99%
See 4 more Smart Citations
“…This is because most of the data collected in this field are obtained with retrospective studies. From this point of view it has been shown that the incidence of primary headache (PH) diagnosis is lower in the ED than in the general population [1][2][3][4][5][6][7][8][9].…”
Section: Prevalencementioning
confidence: 99%
“…The prevalence of migraine diagnosis at discharge from emergency is very variable, ranging from 15 to 32% [3,8,9]. The majority of patients were discharged with a diagnosis of cephalalgia or headache not otherwise specified (NOS) [3,8,9]. J Headache Pain (2005) Abstract Headache is one of the most common reported complaints in the general adult population and it accounts for between 1% and 3% of admissions to an Emergency Department (ED).…”
Section: Prevalencementioning
confidence: 99%
See 3 more Smart Citations